Comparing school age thalassemia children\'s behavioral problem referring to ‎children center in Rasht with their healthy classmates - fatemeh meskiny; minomitra chehrzad; haydeh mahmoodi (Guilan University of Medical Sciences, 2006)
Introduction: Noting children's behavioral problem,‎‏ ‏which formats major forms of children ‎psycho-pathology in all culture and human communities, is very important because most adult ‎behavioral disorder originates from primary experiences in childhood. Behavioral problem ‎have different reasons and one of these reasons are chronic physical illnesses such as major b-‎thalassemia.‎‏ ‏Better recognition of thalassemic children's behavioral problem is the foundation ‎for effective health care planes and prevention of prolonged psycho- behavioral problem in ‎future.‎ Objective: This research was conducted to compare school-age thalassemic children's ‎behavioral problem with their healthy classmates.‎ Methods: This is comparative – descriptive study that ‎‏50‏‎ children with thalassemia referred to ‎children Hospital in Rasht and ‎‏100‏‎ peers with their mothers participated. Data collection tool ‎was a questionnaire including two sections: the first part including demographic characteristics‏ ‏of thalassemic and healthy children and parents, and second part included child behavioral ‎checklist in parent-report that was completed by the mother of the patient. Analysis of Data ‎was done by descriptive statistics (mean and standard deviation) and deductive statistics (c‏2‏‎ – ‎test).‎ Results: Research findings showed that most of suitable behavior at samples research in ‎thalassemic group (‎‏100%‏‎) related to sexual problem and other problem and in health group ‎‎(‎‏100%‏‎) related to social problem, delinquent behavior, aggressive behavior somatic ‎complaints,‎‏ ‏anxiety/depression, though problem, Sexual and other problem.‎‏ ‏Resulths showed ‎that there was significant statistical difference between the two groups in behavioral problem ‎at social problem (P<‎‏0.0001‏‎), aggressive behavioral (P<‎‏0.00001‏‎) Attention problem (P<‎‏0.03‏‎), ‎somatic complaint (P<‎‏0.01‏‎), Anxiety/depression‏ ‏‎(P<‎‏0.0001‏‎) withdrawn (P<‎‏0.0001‏‎).‎ Conclusion: Results showed that most of samples in thalassemic group (‎‏94%‏‎) and healthy ‎group (‎‏100%‏‎) had suitable behavior and statistical c‏2‏‎ – test showed significant difference in ‎behavioral problem between the two groups.‎‏ ‏As well between behavioral problem and ‎demographic characteristics except father age.‎